A Decoupled Control Strategy for a Shunt-Series Modular Multilevel Converter in Wind Energy Conversion System Applications - Rojas-Lobos, F; Diaz-Diaz, M; Pizarro-Jimenez, P (Institute of Electrical and Electronics Engineers Inc., 2021)
In recent years, the rated power of Wind Energy Conversion Systems (WECS) has been growing significantly, to this date, reaching power ratings above 10 MW per wind turbine. Consequently, Modular Multilevel Converters appear as a proper solution to replace conventional power converter in the power conversion stage of multi-megawatts WECS. This paper abords the application of a Shunt-Series Modular Multilevel Converters that interface a single WECS with a medium-voltage AC grid. It is proposed and studied a new control strategy that enables the decoupled operation at both ports of the converter as well as enables to track the maximum power point at the generator side. Simulation results are presented to validate both the proposed topology in WECS application and the control strategy applied. © 2021 IEEE.